The Krugovi Generation about Matoš - Wyszogrodzka-Liberadzka, Natalia (Poznańskie Studia Slawistyczne, 2014)
Antun Gustav Matoš, central figure of Croatian Modernism became an icon and a legend yet in life, which, after the artistʼs death, only strengthened and his influence on the further shape of Croatian literature is difficult to deny. On the other hand, he is not the very often mentioned author the literary journal „Krugovi”, and also he is not considered in the first row of the most influential literary patterns for this generation of writers. However, Antun Gustav Matoš’s image that emerges from the pages of „Krugovi”, although incomplete and fragmentary, is extremely interesting. Young writers attempted to comprehensively educate their literary model reader, so they drew attention to artists who were the most valuable for the native literary tradition. Understanding and acknowledging the importance of his achievements and well-deserved place in the history of Croatian literature, young artists were able, however, to an analytical and critical approach, in the majority of cases presenting a solid argument, not limited to duplication of hackneyed slogans.